Cost Utility of Carbapenemase Producing Enterobacteriaceae (CPE) Screening Strategies in a Low Prevalence Setting. (4th October 2017) - Batra, Rahul; Otter, Jonathan; Edgeworth, Jonathan; Goldenberg, Simon
Abstract: Background: A number of international guidelines recommend screening patients for gastrointestinal carriage of CPE at the point of hospital admission to guide measures aimed at preventing spread (e.g., source isolation, use of personal protective equipment and enhanced environmental decontamination).The cost utility of these screening strategies has rarely been considered. Methods: A cost utility analysis of several screening strategies (non-selective agar, chromogenic selective agar, multiplex PCR (Check-Direct CPE for BDMax™) was undertaken in our low CPE prevalence hospital population using data obtained in a previous extended prevalence study of 4006 consecutive admissions. Results: Non-selective and chromogenic selective agar were significantly less sensitive than PCR, detecting 17% and 67% of true cases, respectively. Screening all admissions using PCR detected all cases at a cost of £4, 417, 595 per year or £34, 328 per case detected. Selective screening using either overseas hospital admission or admission to a high-risk area would have the capacity to detect only 33% and 17% of true cases, respectively, thus are not effective strategies. The method most effective selective screening strategy was to include patients who had been admitted to hospital (UK or overseas) in the last 12 months. Using PCR, this strategy would detect 83% of true cases at a total cost per case detected of £137, 868. The same strategy using chromogenic agar would detect 50% of true cases, at a cost per case detected of £215, 475. Conclusion: Although more expensive, a strategy of screening and presumptively isolating patients with any hospital admission (UK and overseas) in the previous 12 months, rather than using the current Public Health England recommended risk countries and areas, is more effective. When PCR is used this strategy detects 83% of cases compared with 50% with the PHE strategy. Furthermore, it is likely to be easier to implement in practice rather than using a more complicated list of countries and risk areas, which is dependent upon having good epidemiological data to determine international prevalence. Disclosures: All authors: No reported disclosures.